Adsorption of Sulfonamides in Aqueous Solution on Reusable Coconut-Shell Biochar Modified by Alkaline Activation and Magnetization - Sun, Ying; Zheng, Lili; Zheng, Xiaoyan; Xiao, Dao; Yang, Yang; Zhang, Zhengke; Ai, Binling; Sheng, Zhanwu (Frontiers in Chemistry, 2022)
Biochar is a low-cost adsorbent for sorptive removal of antibiotics from wastewater, but the adsorption efficiency needs to be improved. In this study, coconut-shell biochar was activated with KOH to improve the adsorption efficiency and magnetically modified with FeCl3 to enable recycling. The amount of KOH and the concentration of FeCl3 were optimized to reduce the pollution and production cost. The KOH-activated and FeCl3-magnetized biochar gave good sulfonamide antibiotic (SA) removal. The adsorption capacities for sulfadiazine, sulfamethazine, and sulfamethoxazole were 294.12, 400.00, and 454.55 mg g−1, respectively, i.e., five to seven times higher than those achieved with raw biochar. More than 80% of the adsorption capacity was retained after three consecutive adsorption–desorption cycles. A combination of scanning electron microscopy, Brunauer–Emmett–Teller analysis, X-ray diffraction, Fourier-transform infrared and Raman spectroscopies, and magnetic hysteresis analysis showed that KOH activation increased the specific surface area, porosity, and number of oxygen-rich functional groups. Iron oxide particles, which were formed by FeCl3 magnetization, covered the biochar surface. The SAs were adsorbed on the modified biochar via hydrogen bonds between SA molecules and –OH/–COOH groups in the biochar. Investigation of the adsorption kinetics and isotherms showed that the adsorption process follows a pseudo-second-order kinetic model and a monolayer adsorption mechanism. The adsorption capacity at low pH was relatively high because of a combination of π+–π electron-donor–acceptor, charge-assisted hydrogen-bonding, electrostatic, and Lewis acid–base interactions, pore filling, van der Waals forces, and hydrophobic interactions. The results of this study show that magnetically modified biochar has potential applications as an effective, recyclable adsorbent for antibiotic removal during wastewater treatment.